Idarucizumab in dabigatran-treated patients with acute stroke: a review and clinical update - Frol, Senta; Pretnar Oblak, Janja; Šabovič, Mišo; Ntaios, George; Kermer, Pawel (Frontiers in Neurology, 2024)
Idarucizumab is an antibody fragment specific for the immediate reversal of dabigatran anticoagulation effects. The use of idarucizumab is approved for dabigatran-treated patients suffering from life-threatening or uncontrolled bleeding and those in need of urgent surgery or invasive procedures. Data from randomized controlled clinical trials and real-world experience provide reassuring evidence about the efficacy and safety of idarucizmab use in patients with acute stroke. In this narrative review, we summarize the available real-world evidence and discuss the relevance and importance of idarucizumab treatment in acute stroke patients in everyday clinical practice. In addition, we also discuss special issues like prothrombin complex concentrate application as an alternative to idarucizumab, its application before endovascular therapy, sensitivity of thrombi to lysis, and necessary laboratory examinations.